Transportation, dispersion and ordering of dense colloidal assemblies by magnetic interfacial rotaphoresis1. Issue 13 (7th July 2015) - van Reenen, A.; de Jong, A. M.; Prins, M. W. J.
<x xml:space="preserve">Abstract</x> We reveal a method to transport, disperse and order dense assemblies of magnetically responsive colloids on a surface within seconds and with velocities of mm s−1.